The Role of Leukocytes in Diabetic Cardiomyopathy - Bajpai, Anamika; Tilley, Douglas G. (Frontiers in Physiology, 2018)
Diabetes is predominant risk factor for cardiovascular diseases such as myocardial infarction and heart failure. Recently, leukocytes, particularly neutrophils, macrophages and lymphocytes, have become targets of investigation for their potential role in a number of chronic inflammatory diseases such as diabetes and heart failure. While leukocytes contribute significantly to the progression of diabetes and heart failure individually, understanding their participation in the pathogenesis of diabetic heart failure is much less understood. The present review summarizes the role of leukocytes in the complex interplay between diabetes and heart failure, which is critical to the discovery of new targeted therapies for diabetic cardiomyopathy.